Comunidades Kalunga e Jardim Cascata: realidades, perspectivas e desafios para o ensino de química no contexto da educação escolar quilombola - Franzão, Juliana Moraes (2017)
For this work, a research was carried out to answer the question: "What are the realities, perspectives and challenges of Chemical Education in Quilombola School Education versus the National Curricular Guidelines for Quilombola Elementary Education in Basic Education (DCNEEQEB)? ". To answer this question, a study was accomplished in the High School classes of two Remnant Communities of Quilombo of the State of Goiás, State School Jardim Cascata, located in the JardimCascata neighborhood, to attend the Quilombola Community Jardim Cascata and Delfiori, at the city of Aparecida de Goiânia, and in six schools at the Kalunga Quilombola Community, located in the rural areas of Cavalcante, Monte Alegre de Goiás and Teresina de Goiás municipalities. Data collection took place through coexistence, dialogue, semi-structured interviews, and Chemistry classes done with students from the community along with members of each community. The methodology used focuses on the qualitative ethnographic research in which a case is studied in depth, while in the data collection, a qualitative approach was used. The work involved 6 schools that offer secondary education in the Kalunga Territory of Goiás and 1 school in Aparecida de Goiânia, 3 School Directors, 2 Pedagogical Coordinators, 7 ChemistryTeachers, the School’scommunity (High School Students, Mess Room Staff, General Services, Secretaries), Matriarch and Retired Teachers of the Kalunga Community, Members of the Quilombola Kalunga Community, President of the Quilombola Urbana Jardim Cascata Association and Community Members. The research was developed in three stages, the first one occurred at the JardimCascata State School, further with the students of the Education of Young and Adults, High School level, enrolled in the 1st, 2nd, 3rd and 4th periods, Chemistry teacher, and members of the Quilombola Community and Urban Community Jardim Cascata, with participation in the activities of the School, giving priority to the follow-up of Chemistry classes, elaboration and accomplishment of classes in the classrooms mentioned, application of questionnaire and interviews. In the second stage of this study, simultaneously with the research carried out in the first stage, we looked for other schools to continue the data collection. The continuity of the study was carried out in the State Schools of the Quilombola Kalunga Community, located in the countryside, along with its student communities and social communities. As a result of the research, it was found that schools have several similarities, even though one is urban and the other in the countryside. All schools are classified as quilombolas for they are located inquilombolas territories, they have a Reference School Curriculum, which is used for Teaching Chemistry in all State Schools of the State of Goiás, and they lack Pedagogical Political Projects of the schools that come to dialogue with the needs of schools, especially in the modality of Youth and Adult Education. The research proposes the need to create Undergraduate Courses in Quilombola Discipline, offer Training Courses for teachers who work in Quilombola School Education and production of didactic-pedagogical materials for the teaching of Chemistry that dialogue with the quotidian of the Quilombo RemnantCommunities, valuing the traditional knowledge existing in the communities and that can be used in class as a way to bring the student closer to his own reality, placing him as the protagonist of his school formation process. In this way, Teaching Chemistry will contribute to scientific literacy that maintains, rescues and values the cultures of the students overcoming the difficulties related to their historical process of struggles and allowing the true recognition and pride of its people.